2022
DOI: 10.1021/acs.est.2c01404
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker-Determined Nonylphenol Exposure and Associated Risks in Children of Thailand, Indonesia, and Saudi Arabia

Abstract: Nonylphenol (NP) is an endocrine disruptor and environmental contaminant. Yet, data on individual body burdens and potential health risks in humans, especially among children, are scarce. We analyzed two specific urinary NP metabolites, hydroxy-NP (OH-NP) and oxo-NP. In contrast to parent NP, OH-NP has a much higher urinary excretion fraction (F ue), and both are insusceptible to external contamination. We investigated spot urine samples from school children of Thailand (n = 104), Indonesia (n = 89), and Saudi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 89 publications
0
4
0
Order By: Relevance
“…Since attitude was found to exert the largest impact on purchase intention, more attention should be paid to shaping consumer attitudes in the process of promoting sustainable food consumption. It should be highlighted that though online takeout is fast and convenient, it comes with great potential health risks, such as microplastics (Liu et al, 2019 ; Prata, 2018 ; Ali et al, 2021 ), plasticizers (Freire et al, 2006 ; Ringbeck et al, 2022 ), and other additives (Segovia‐mendoza et al, 2022 ) in plastic packaging are harmful to the human body. In addition, the rate of recycling of plastic takeout packaging cannot keep up with the rapidly increasing rate of takeout orders (Liu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since attitude was found to exert the largest impact on purchase intention, more attention should be paid to shaping consumer attitudes in the process of promoting sustainable food consumption. It should be highlighted that though online takeout is fast and convenient, it comes with great potential health risks, such as microplastics (Liu et al, 2019 ; Prata, 2018 ; Ali et al, 2021 ), plasticizers (Freire et al, 2006 ; Ringbeck et al, 2022 ), and other additives (Segovia‐mendoza et al, 2022 ) in plastic packaging are harmful to the human body. In addition, the rate of recycling of plastic takeout packaging cannot keep up with the rapidly increasing rate of takeout orders (Liu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Even though the toxicity of most plasticizers is low, long-term exposure can still cause significant damage to the human body. Study on PAEs residue in children from various countries has confirmed that plasticizer PAEs keeps accumulating in the body for a long time, leading to human complications (Ringbeck et al, 2022 ). Besides, PAEs can enter the body through food contact, skin contact, and breathing.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Breast milk is among the body fluids most suitable for monitoring the effect of alkylphenol exposure on both mother and child [16]. Breast milk is a complex and variable fluid that evolved to nourish the infant and protect it from disease while its immune system continues to develop.…”
Section: Introductionmentioning
confidence: 99%
“…Breast milk is among the body fluids most suitable for monitoring the effect of exposure to alkylphenols to both mother and child [14]. Breast milk is a complex and variable fluid that evolved to nourish the infant and protect it from disease while its immune system continues to develop.…”
Section: Introductionmentioning
confidence: 99%